Protecting Patients’ Health Records using Block chain Technology - Niti Dey (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The world is advancing, and the progress necessitates a robust community for sustainable development. Healthcare data represents forecasts of an individual’s well-being over time. Breaches in information occur due to the centralized approach to storing hospital records. According to the 2017 Phenomenon Cost of Data Breach Research, the cost of a security breach for healthcare entities is estimated to be 380 per record. Personal client information, such as names, addresses, and medical conditions, is frequently compromised in the era of smart homes and cities, which is inversely correlated with the security of Electronic Health Records (EHRs). Users often encounter difficulty accessing data due to the sophisticated privacy measures already implemented for EHRs. These systems must strike a delicate balance between the need for regular data interaction among users and healthcare providers, and safeguarding data. Blockchain technology addresses these challenges by distributing data in a decentralized and secure manner. It is utilized in healthcare to maintain the equilibrium between the availability and security of EHRs. This article introduces a Blockchain-based e-Health Report Management Model (BC-EHRMM) to effectively manage and preserve EHRs. Moreover, it provides patients, clinicians, and third parties with convenient and secure access to healthcare records while ensuring patient confidentiality. The research discussed in this article examines how it meets the needs of patients, clinicians, and other stakeholders, while addressing privacy and security concerns in healthcare 4.0.